1992
DOI: 10.1007/bf00265916
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacology and the provision of drug information

Abstract: Clinical pharmacologists have a service role in the provision of drug information to individuals both in hospitals and primary health care. We present here a systematic approach in answering questions in a drug information centre (DIC), and describe the working method and the documentation of the work in a question answer (Q/A) data base. Drugline is a full-text data base offering problem-oriented drug evaluation comparable to a clinical consultation. The drug information is produced in a non-commercial drug i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…POD is an answering service for the physician where the information is designed to include a discussion of the specific patient problem rather than to purely retrieve and forward pertinent literature. The information is typically provided by clinical pharmacologists or pharmacists with expertise in literature retrieval and appraisal [12][13][14][15], and the working method has much in common with the concept of EBM. A few studies have shown that POD has an impact on clinical practice [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…POD is an answering service for the physician where the information is designed to include a discussion of the specific patient problem rather than to purely retrieve and forward pertinent literature. The information is typically provided by clinical pharmacologists or pharmacists with expertise in literature retrieval and appraisal [12][13][14][15], and the working method has much in common with the concept of EBM. A few studies have shown that POD has an impact on clinical practice [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of this clinical pharmacology activity has been discussed in terms of high technology availability [4,5]. A systematic approach in providing evaluated and problem-oriented drug information by the Drug Information Centre (DIC) studied here was presented in this journal [6]. The aim of the DIC is to answer questions about drug treatment A. LLerena ([]) …”
mentioning
confidence: 99%
“…A register of all Q&As handled by the DIC at the Karolinska University Hospital, Huddinge, was used as the information source for this study [2,18]. When a question is asked, a literature search is performed at the DIC, the available information is evaluated and initially a preliminary answer is given.…”
Section: Settings and Subjectsmentioning
confidence: 99%
“…After internal review and approval at a weekly staff meeting a written answer with references is sent to the requester [18]. All Q&As are continuously registered in a local database, Dataease, which contains information concerning question date, questioner, demographic data, drug and medical history of the patient, and the drug related problem in question (adverse reaction, interaction, kinetics, drug choice and/or dosing, or drug formulation and/or administration) and the answer delivered with literature references [2,18]. The Q&As of general interest are put into an international database, Drugline, that is continually updated by the DICs in Sweden, Odense Denmark and Åbo, Finland [19].…”
Section: Settings and Subjectsmentioning
confidence: 99%
See 1 more Smart Citation